UNDERSTANDING MICRO FARMERS’ MOTIVATIONS AND DECISIONS ON CHALLENGES FACED IN MALAYSIA - Akmal Aini Othman; Jaslin Md Dahlan; Syaidatul Zarina Mat Din; Rosmah Abd Ghani@Ismail; Norfariza Mohd Ali (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Despite years of industrialisation, Johor is still a leader in agriculture. The state is Peninsular Malaysia’s major agricultural producer, and it has the third-highest official agricultural productivity in Malaysia. The growing of oil palms, various fruits and vegetables, poultry, pigs, cut flowers, and ornamental fish are among Johor’s top agricultural strengths. This study brings new understanding to the existing literature, highlights new ways of looking at Malaysian micro farmers. Through this study, a better understanding of the challenges faced by micro farmers. Several sessions of semi-structured interviews were conducted with the selected farmers. Due to the Controlled Movement Order, we had to carry out the interviews via Google Meet. That was a great challenge in our data collection. The problems identified from this study are market price of crops, ownership of land, quality of crops, latex yield, pest infestation and workforce. Unlike the larger plantations, they depend on government subsidies and assistance during the trying times. They also made suggestions to overcome day-to-day farming challenges that may help them improve their economic and personal life for themselves and their families.